Cultural Studies in a Globalizing World: An Investigation of Communicative Codes - قاسم، مجيب علي مرشد; مطهر، عباس عبدالملك محمد (جامعة الأندلس للعلوم والتقنية, 2022)
يقدم البحث مجموعة متنوعة من المصطلحات المتداخلة في المجال الواسع للدراسات الثقافية مثل "الدراسات الثقافية" و "النقد الثقافي" و "المادية الثقافية"، وباستخدام المنهج الوصفي التحليلي يهدف إلى توضيح كيفية عمل الثقافة من خلال رموز تواصلية مهمة في بيئات ثقافية متعددة يتعلمها البشر طيلة حياتهم لإكسابهم التقاليد والعادات والأدوار الاجتماعية، وكيف أن الدراسات الثقافية أصبحت تخصص ومدرسة للنقد أدت بدورها إلى تغيير طريقة دراسة الأدب. فالرموز الثقافية التي يجري ممارستها مثلا في مجال الطقوس الدينية والأنشطة والتجارب اليومية وغيرها تصبح معرفة أساسية وأجزاء مسجلة في تاريخ ذلك المجتمع. ويرمي البحث إلى تقديم صورة واضحة حول معرفة الرموز الثقافية ووظائفها الاجتماعية وكيف أنها تمكن الأفراد من إدراك وفهم الثقافة والأدب فهما شاملا وتصبح مرجعا منهجيا لثقافة ذلك المجتمع. وتضمن البحث سرد تطور الدراسات الثقافية في أواخر القرن الماضي، حيث تم وضع الأسس لقبولها في المجال الأكاديمي، مما مهد الطريق لإعادة بناء الأعمال الأدبية وإعادة تقديرها بالإشارة إلى مجالها الثقافي. ويسعى البحث إلى الإجابة عن بعض الأسئلة منها ما إذا كانت الدراسات الثقافية تساعدنا في استكشاف وظائف النواتج الثقافية في مجتمع أو عمل أدبي معين، مع تقديم أمثلة لبعض الرموز الثقافية وكيف تساعدنا في قراءة وتعريف الفرد إقليميا واجتماعيا واقتصاديا ودينيا. وتشدد الخاتمة على القراء والنقاد والمترجمين أن يكونوا على دراية بالرموز الثقافية عند التعامل مع المجتمعات الأخرى أو القراءة أو الترجمة عنها. This paper presents a diversity of overlapping terms under the broad area of Cultural Studies like 'culture studies', ‘cultural criticism’, and 'cultural materialism'. Through a descriptive analytical method, this study aims to show how culture operates by significant communicative codes in multicultural settings that humans learn from cradle to grave, acquiring cultural traditions, customs, and social roles. As a discipline and a school of criticism, Cultural Studies has changed the way of the study of literature. Those practiced cultural codes of religious rituals, daily activities, experiences, among others, have become the primary knowledge and recorded parts of the history of a particular society. It depicts a clear picture of how the knowledge of cultural codes and their social functions enable individuals to perceive culture and literature comprehensively and make a systematized reference to the culture of that particular society. It shows the development of Cultural Studies, late last century, laying its foundations to be accepted in the academic field, which paved the way for literary works to be reconstructed, re-appreciated, and reassigned in reference to their cultural field. This paper attempts to answer some questions about Cultural Studies and whether it can help us explore the functions of cultural products in a society or a literary work. It provides examples of some cultural codes and how they help us read and identify an individual regionally, socially, economically, and religiously. The Conclusion stresses on readers, critics and translators to be aware of the cultural codes when dealing with, reading of or translating from other societies.
Keywords: عصر العولمة -- السلوكيات الثقافية -- الهوية الثقافية -- العولمة الثقافية